2022
DOI: 10.1029/2021ja029848
|View full text |Cite
|
Sign up to set email alerts
|

African and American Equatorial Ionization Anomaly (EIA) Responses to 2013 SSW Event

Abstract: This study investigates the responses of the African and American Equatorial Ionization Anomaly (EIA) regions to 2013 Sudden Stratospheric Warming (SSW) event. The Total Electron Content (TEC) data obtained from chains of Global Positioning System receivers within ±40° geomagnetic latitudes in the African and American sectors were used to construct the EIA structures for both longitudinal sectors. The responses of the EIA structures, constructed from the TEC, ΔTEC, and ionospheric irregularities data to the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 75 publications
0
6
2
Order By: Relevance
“…The remaining storms (1 January, 18 February, 16 March, and 20 March) investigated (Figure 6) showed a negative EIA TEC signature. These negative EIA TEC features are contrary to the recent report of the positive ionospheric response in the American sector for the 2013 SSW event (Idolor et al, 2022). Idolor et al (2022) reported that the impact of the PPEF on the ionosphere just around sunset enhances the eastward electric field via the vertical E X B drift leading to the enhancement of the EIA TEC profile (Tsurutani et al, 2008).…”
Section: Figure 10contrasting
confidence: 93%
See 4 more Smart Citations
“…The remaining storms (1 January, 18 February, 16 March, and 20 March) investigated (Figure 6) showed a negative EIA TEC signature. These negative EIA TEC features are contrary to the recent report of the positive ionospheric response in the American sector for the 2013 SSW event (Idolor et al, 2022). Idolor et al (2022) reported that the impact of the PPEF on the ionosphere just around sunset enhances the eastward electric field via the vertical E X B drift leading to the enhancement of the EIA TEC profile (Tsurutani et al, 2008).…”
Section: Figure 10contrasting
confidence: 93%
“…Modeling results using the thermosphereionosphere-mesosphere-electrodynamics general circulation model (TIME-GCM) of the vertical drifts for the 2013 SSW event showed a significant increase in daytime vertical drift of ~100% associated with the moderate geomagnetic storm occurrence for the American sector (Maute et al, 2015). A similar report of positive ionospheric response in the TEC was presented in the American sector and negative ionospheric TEC response in the African sector associated with the overlap of the moderate geomagnetic storm with the 2013 SSW event (Idolor et al, 2022). Several studies have also shown an increase in TEC enhancement at the equatorial ionization anomaly (EIA) crest regions during some of the SSW events in the American sector (Goncharenko et al, 2013;Paes et al, 2014), while the EIA TEC suppression have been reported in the Brazilian sector (De Jesus et al, 2017b;Vieira et al, 2017).…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations